THE IMPORTANCE OF USER INTERFACE DESIGN IN REAL ESTATE PLATFORMS (International Seven Journal of Multidisciplinary, 2024)
User Interface (UI) design is a key factor in the success of digital platforms, particularly in the real estate sector, where market competitiveness and complexity demand an efficient and intuitive user experience. UI not only facilitates navigation but also influences how users interact with the platform, filter preferences, view properties, and make transactions. A simple and functional design, combined with a logical organization of information, is crucial for smooth, frustration-free navigation. Elements like clear menus, accessibility, and efficiency in property searches are essential for user retention and building trust. Moreover, interactive features such as virtual tours and high-quality videos enhance the user experience and assist in making more informed decisions, especially in a sector with significant financial implications like real estate. Research studies, such as those by Manko (2021) and Kandil et al. (2021), highlight the importance of creating an intuitive and efficient experience to attract and retain users, which becomes increasingly relevant with technological advancements. Yuan et al. (2013) suggest that personalized recommendation systems based on user behavior are an effective solution to optimize searches and increase customer satisfaction. Continuously adapting to users’ preferences, using online review data, is vital for improving the platform and strengthening its competitiveness. In a saturated digital market, investing in intuitive design and interactive features is not just an aesthetic concern, but a vital strategy for the success of real estate platforms.